Developmental Variation in Amylase Allozyme Activity Associated with Chromosome Inversions in DROSOPHILA PERSIMILIS - Norman, R. A. (1980)
The amylase locus in Drosophila persimilis is polymorphic for allozymes, two of which show associations with naturally occurring chromosome 3 inversions. Amy(1.09) occurs at high frequencies only in Whitney (WT), while the other common arrangements—Standard (ST), Klamath (KL) and Mendocino (MD)—are predominantly Amy (1.00). We have examined numerous strains, representing various electromorphs and inversions, for variation in cis-specific activity expression in both third-instar larvae and adults. Comparisons of these two life stages also allows the survey of developmental variation in amylase activities. The amount of activity variation exceeds electrophoretic variation at this locus. Moreover, this variation is largely nonrandom and reveals more genic divergence among inversions. The 1.00 allozyme of MD is more active than 1.00 KL in larvae and adults and shows a different developmental pattern. The activity of the 1.00 allozyme of KL is greater than 1.00 allozyme of ST in larvae and adults, but these two arrangements have similar developmental patterns. WT 1 with a 1.00 allele is dramatically different from the 1.00 allozymes of other arrangements in its developmental pattern. The 1.09 allozyme has high activity in WT and KL, but these arrangements differ in their developmental pattern of expression, WT being more active in adults. F(2) segregational analyses are consistent with the variation being due to either structural enzyme variants or closely linked cis-acting regulatory elements. We argue that the suppression of recombination between arrangements has allowed the divergence in amylase activity among inversions.